Implementasi Shalat Dhuha untuk Meningkatkan Karakter Islami di SDN Pagermaneuh Lembang - Risya Jannati Saniyyah; Mujahid Rasyid; Huriah Rachmah (Bandung Conference Series: Islamic Education, 2024)
Abstract This research is motivated by the lack of manners that students have, as well as the lack of religious knowledge. religious knowledge of Pagermaneuh Lembang Elementary School, whichaims to determine the existence of an increase in the Islamic character of students with the implementation of dhuha prayer. This study uses a qualitative approach with a descriptive method. Data collection methods include observation, interviews, and documentation. The data analysis uses data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the increase in Islamic character has increased quite well. This can be seen from the implementation of duha prayer at SDN Pagermaneuh Lembang, which is carried out for four days a week, namely Tuesday, Wednesday, Thursday, and Friday. In addition, there is an evaluation of the duha prayer program, namely the discipline of coming to school and the sense of responsibility of teachers towards students. Supporting factors for the implementation of duha prayer at SDN Pagermaneuh Lembang include encouragement from teachers and parents, the availability of adequate facilities, and social media (WhatsApp) as a communication tool to monitor students in duha prayer during holidays. Inhibiting factors for the implementation of duha prayer at SDN Pagermaneuh Lembang include laziness among students, a lack of facilities and infrastructure, and the fact that there are still students who do not bring prayer equipment. So it can be concluded that the implementation of duha prayer at SDN Pagermaneuh Lembang has been effective in improving the Islamic character of students. Abstrak. Penelitian ini dilatarbelakangi oleh kurangnya sikap sopan santun yang siswa miliki di SDN Pagermaneuh Lembang yang bertujuan untuk mengetahui adanya peningkatan karakter Islami siswa-siswai dengan adanya implementasi shalat dhuha. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Metode pengumpulan data dengan menggunakan observasi, wawancara dan dokumentasi. Adapun analisis datanya menggunakan pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa peningkatan karakter Islami sudah mengalami peningkatan yang cukup baik. Hal tersebut dapat terlihat dari implementasi shalat dhuha di SDN Pagermaneuh Lembang yang dilaksanakan selama 4 hari dalam seminggu yaitu hari Selasa, Rabu, Kamis dan Jum'at. Selain itu ada evaluasi dari program shalat dhuha yaitu adanya kedisiplinan datang ke sekolah dan rasa tanggung jawab guru terhadap siswa-siswi. Faktor pendukung dari implementasi shalat dhuha di SDN Pagermaneuh Lembang diantaranya adanya dorongan dari guru, orang tua, tersedianya fasilitas yang memadai, serta media sosial (whatsapp) sebagai alat komunikasi untuk memantau anak dalam shalat dhuha ketika libur. Faktor penghambat implementasi shalat dhuha di SDN Pagermaneuh Lembang diantaranya adanya rasa malas terhadap siswa-siswi, kurangnya sarana prasarana serta masih ada siswa yang tidak membawa alat shalat. Maka dapat disimpulkan bahwa implementasi shalat dhuha di SDN Pagermaneuh Lembang sudah efektif dalam meningkatkan karakter Islami siswa-siswi